2016
DOI: 10.4093/dmj.2016.40.6.494
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Susceptibility to Diabetes Using Features of the Adipose Tissue in Response toIn UteroPolycyclic Aromatic Hydrocarbons Exposure

Abstract: BackgroundIn recent times, there has been an increase in the incidence of type 2 diabetes mellitus (T2DM) particularly in children. Adipocyte dysfunction provide a critical link between obesity and insulin resistance resulting in diabetes outcome. Further, environmental chemical exposure during early years of life might be a significant contributing factor to the increase in the incidence of T2DM. This study tests the idea that exposure to environmental contaminants (2-aminoanthracene [2AA]) in utero will show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The methods employed for hematoxylin and eosin (H&E) and immunohistochemistry (IHC) staining for CD68 have been previously published (Gato et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods employed for hematoxylin and eosin (H&E) and immunohistochemistry (IHC) staining for CD68 have been previously published (Gato et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Based on recent studies, interference in the intrauterine environment may increase the susceptibility to T2DM. That is, environmental exposures in one's childhood may increase the risk of chronic diseases in adulthood (Gato et al, 2016). Previous studies in Sprague Dawley rats from ingestion of 2AA resulted in damage to the immune system and symptoms that mimic the characteristics of diabetes (Wilson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this article, Gato et al [7] reported the influence of 2AA exposure to the fetus, with special focus on the changes of adipose tissue. They analyzed pups and pregnant dams from control to high dose of 2AA exposure (0 to 100 mg/kg) in regular diet group and in moderate to high fat diet group.…”
mentioning
confidence: 99%
“…Even if 2AA had influences on insulin resistance and glucose metabolism, the results of exposure of 2AA in pregnant animals and direct effects on fetus are rare and interesting. We have several questions for your work [7]. …”
mentioning
confidence: 99%
“…We appreciate your interest and comments on our article entitled “Investigating susceptibility to diabetes using features of the adipose tissue in response to in utero polycyclic aromatic hydrocarbons exposure” that was published in Diabetes & Metabolism Journal [1]. …”
mentioning
confidence: 99%